2016
DOI: 10.1152/ajplung.00288.2015
|View full text |Cite
|
Sign up to set email alerts
|

The TLR7 agonist imiquimod induces bronchodilation via a nonneuronal TLR7-independent mechanism: a possible role for quinoline in airway dilation

Abstract: Their recently reported ability to rapidly relax airways has further increased their interest in the treatment of pulmonary disease. However, the mechanisms behind this effect are not fully understood. The present study, therefore, aimed to determine whether airway smooth muscle (ASM)-dependent mechanisms could be identified. TLR7 agonists were added to guinea pig airways following precontraction with carbachol in vitro or histamine in vivo. Pharmacological inhibitors were used to dissect conventional pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…In addition, activation of sensory neurons by imiquimod has been shown to be TLR7 independent (6), which suggests that a TLR7-dependent neuronal mechanism of relaxation does not occur via sensory neurons. We could further demonstrate in our study that all nerve-mediated relaxation was blocked by TTX (9). NOreleasing inhibitory nonadrenergic, noncholinergic (iNANC) fibers have repeatedly been shown to be TTX sensitive (10), suggesting that our use of TTX was sufficient to evaluate and discount the possible contribution of NO-mediated neuronal relaxation, the mechanism proposed by Drake and colleagues.…”
supporting
confidence: 67%
See 2 more Smart Citations
“…In addition, activation of sensory neurons by imiquimod has been shown to be TLR7 independent (6), which suggests that a TLR7-dependent neuronal mechanism of relaxation does not occur via sensory neurons. We could further demonstrate in our study that all nerve-mediated relaxation was blocked by TTX (9). NOreleasing inhibitory nonadrenergic, noncholinergic (iNANC) fibers have repeatedly been shown to be TTX sensitive (10), suggesting that our use of TTX was sufficient to evaluate and discount the possible contribution of NO-mediated neuronal relaxation, the mechanism proposed by Drake and colleagues.…”
supporting
confidence: 67%
“…TO THE EDITOR: We recently published a study investigating the bronchodilatory capacity of the Toll-like receptor 7 (TLR7) agonist imiquimod, establishing the presence of a nonneuronal, TLR7-independent mechanism of dilation (9). Our study adds new information to the previously published reports, which demonstrated that relaxation can be mediated by a TLR7-dependent release of nitric oxide (NO) from innervating nerves (2,5).…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…Although the effects of TLR9 on the activity of SERCA2 are different from ours, these findings suggested that an alternative TLR signalling pathway, in addition to the canonical TLR-nuclear factor-B axis, likely exists. In contrast, Larsson and colleagues have recently reported that R837 may induce [Ca 2+ ] i release from ER stores in human airway smooth muscle cells (ASMCs) via a TLR7-independent mechanism (Larsson et al, 2016). Although we are not fully able to explain this discrepancy, this is probably because our study was performed in a different manner.…”
Section: Discussionmentioning
confidence: 60%
“…In addition to the Th2 modulating effect, TLR7 agonists relax human airway smooth muscle strips in vitro (Drake et al 2013) previously modelled only in animals (Drake et al 2013;Ekman, Adner & Cardell 2011;Kaufman, Fryer & Jacoby 2011). Interestingly, the mechanism of bronchodilation may be independent of TLR7 signalling and instead signify an off-target effect of the quinoline containing TLR7 agonists (Larsson et al 2016), further supporting the development of TLR7/8 agonists as asthma medications.…”
Section: How Consistent Is the Evidence For Interferon Deficiency In mentioning
confidence: 96%